CREATIVE IMAGE OF VAGIF MUSTAFAZODA (British Journal of Global Ecology and Sustainable Development, 2024)
This article highlights the creative work of Vagif Mustafazoda, a brilliant exponent of the ethno-jazz style, his works based on ethno-Jazz, his role in music culture and aesthetics. This article also covers the peculiarity of the composer's works, the influence of his works on the human soul.